2012
DOI: 10.1002/lary.23277
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of topical fluorescein helpful for management of CSF leakage?

Abstract: Cases with traumatic CSF leakage pose a higher risk of meningitis than the cases with spontaneous CSF leakage. Topical application of fluorescein is highly specific and sensitive in identifying preoperative, intraoperative, and postoperative CSF leakage. It is a simple, quick, and sensitive technique. The surgeon should be vigilant for multiple defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…Over the past 3 decades, multiple studies have demonstrated the safety and efficacy of endoscopic repair, with consensus that endoscopic repair should be considered the standard of care . Both intrathecal and topical use of fluorescein may augment intraoperative identification of a CSF fistula, though intrathecal usage has been associated with rare, but potentially serious complications . Nuances of surgical repair and postoperative intracranial pressure management are reviewed in the following sections.…”
Section: Primary Csf Rhinorrheamentioning
confidence: 99%
“…Over the past 3 decades, multiple studies have demonstrated the safety and efficacy of endoscopic repair, with consensus that endoscopic repair should be considered the standard of care . Both intrathecal and topical use of fluorescein may augment intraoperative identification of a CSF fistula, though intrathecal usage has been associated with rare, but potentially serious complications . Nuances of surgical repair and postoperative intracranial pressure management are reviewed in the following sections.…”
Section: Primary Csf Rhinorrheamentioning
confidence: 99%
“…Currently, high-resolution CT scan, MRI scan, CT cisternography, MR cisternography, radionuclide cisternography, intrathecal fluorescein, and biochemical tests including b-2 transferrin or sugar and protein analysis are combined to detect CSF leakage. [15][16][17] In our study, we used a combination of the current techniques including b-2 transferrin analysis and MRI scan, high-resolution CT scan was also underwent in particular cases. We established correct diagnosis of the presence of CSF rhinorrhea preoperatively in 29 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups advocate for topical fluorescein in the localization of CSF rhinorrhea. These authors describe a color change in nasal pledgets from yellow‐brown to green as evidence of an active CSF leak . Although the success rates of topical fluorescein are reported as high as 100%, no studies have specifically evaluated the possibility of false‐positive results with blood products, mucus, or nasal secretions .…”
Section: Discussionmentioning
confidence: 99%
“…These authors describe a color change in nasal pledgets from yellow‐brown to green as evidence of an active CSF leak . Although the success rates of topical fluorescein are reported as high as 100%, no studies have specifically evaluated the possibility of false‐positive results with blood products, mucus, or nasal secretions . Furthermore, this test is only effective over applied areas; ie, if the patient has multiple skull‐base defects but only 1 is suspected it may be missed if only 1 area of the cranial base is investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation